2010
DOI: 10.1175/2009jcli3053.1
|View full text |Cite
|
Sign up to set email alerts
|

The Seasonal Atmospheric Response to Projected Arctic Sea Ice Loss in the Late Twenty-First Century

Abstract: The authors investigate the atmospheric response to projected Arctic sea ice loss at the end of the twentyfirst century using an atmospheric general circulation model (GCM) coupled to a land surface model. The response was obtained from two 60-yr integrations: one with a repeating seasonal cycle of specified sea ice conditions for the late twentieth century and one with that of sea ice conditions for the late twentyfirst century (2080-99). In both integrations, a repeating seasonal cycle of SSTs for 1980-99 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

70
409
7
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 482 publications
(508 citation statements)
references
References 35 publications
70
409
7
1
Order By: Relevance
“…Thus, the improper setting of the winter sea-ice reduction in the model might have an impact on the results of the winter atmosphere circulation changes and the related weather events in response to the autumn seaice retreat. The JF responses in our simulation are different from previous studies (Deser et al 2010;Liu et al 2012;Semmler et al 2012) which reported simulated negative winter AO. One of the possible reasons is that the winter sea-ice variations were evolved into the model simulations in those studies.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Thus, the improper setting of the winter sea-ice reduction in the model might have an impact on the results of the winter atmosphere circulation changes and the related weather events in response to the autumn seaice retreat. The JF responses in our simulation are different from previous studies (Deser et al 2010;Liu et al 2012;Semmler et al 2012) which reported simulated negative winter AO. One of the possible reasons is that the winter sea-ice variations were evolved into the model simulations in those studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Since there is no perturbation of the boundary conditions from mid December to early August and the atmosphere processes are short persistent, it can be treated that the autumn-winter responses in each year is independent from the responses in previous year. Similar configuration for the boundary conditions has been used in previous studies (Deser et al 2010;Liu et al 2012;Screen et al 2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the relative warmth of the land surface in much of the Northern Hemisphere exceeds 1.0ÂșC. This is consistent with the results of Deser et al (2010) who found that heat released from the Arctic Ocean under reduced sea-ice conditions is communicated to the Arctic atmospheric boundary layer by transients. The warming of the Southern Hemisphere land surface is limited except in Antarctica.…”
Section: Annual Mean and Annual Cyclesupporting
confidence: 90%
“…Snow and ice cover have a large influence on both the local and remote climate (Magnusdottir et al 2004;Alexander et al 2004;Koenigk et al 2009;Deser et al 2010;Overland and Wang 2010). The export of freshwater from the Arctic alters the deep water formation in the North Atlantic (HĂ€kkinen 1999;Haak et al 2003;Koenigk et al 2006).…”
Section: Introductionmentioning
confidence: 99%